Indicators of Blood Composition in Type 2 Diabetes - Sobirova Dildora Ravshanovna (Scholars Digest Publishing, 2023)
This article explores the critical indicators of blood composition in individuals with type 2 diabetes, shedding light on the complex interplay between metabolic dysregulation and hematological parameters. Type 2 diabetes is a prevalent metabolic disorder characterized by impaired glucose homeostasis, which can significantly impact blood composition. The article delves into key hematological markers such as hemoglobin A1c (HbA1c), lipid profile, glucose levels, insulin resistance, and inflammatory markers. Additionally, it examines the clinical relevance of these indicators, their utility in diabetes management, and their potential as predictive tools for complications associated with type 2 diabetes. By elucidating the relationship between blood composition and type 2 diabetes, this article contributes to a deeper understanding of the disease and offers insights into improved management and prevention strategies.
Keywords: Type 2 diabetes, Blood composition, Hematological indicators, Hemoglobin A1c, Lipid profile, Glucose levels, Insulin resistance, Inflammatory markers, Diabetes management, Complications prevention.